2011
DOI: 10.1007/s11269-011-9813-2
|View full text |Cite
|
Sign up to set email alerts
|

Critical Flow for Water Management in a Shallow Tidal River Based on Estuarine Residence Time

Abstract: To support the development of protective water resources management strategies, a 3D hydrodynamic model was applied to the Little Manatee River (LMR) to evaluate the effects of reducing river flow and drought on the Estuarine Residence Time (ERT). ERT is an important indicator for estuarine environmental quality. The Little Manatee River is a small tidal river estuary with a yearly mean gaged freshwater inflow of 4.8 m 3 /s. The hydrodynamic model was calibrated and verified by using two continuous data sets f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…As expected, and observed in similar studies in the literature, Rt is a physical parameter directly dependent on, and sensitive to, the physical features of waterbodies and of their seasonal variations. Therefore, it has been used as important primary indicator in studies related to the quality of the water [25][26][27][28][72][73][74][75][76][77][78].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, and observed in similar studies in the literature, Rt is a physical parameter directly dependent on, and sensitive to, the physical features of waterbodies and of their seasonal variations. Therefore, it has been used as important primary indicator in studies related to the quality of the water [25][26][27][28][72][73][74][75][76][77][78].…”
Section: Discussionmentioning
confidence: 99%
“…during neap tides (3-4 m; Yuan et al 2007). Liu et al (2008) for the Danshuei River Estuary (Taiwan), which is at the lower end of the macrotidal range, and by Huang et al (2011) for the microtidal Little Manatee Estuary, Florida, USA, demonstrated that residence time decreases with increasing freshwater inflow ( Figure 7). These trends were described effectively by an exponential regression equation (r 2 = 0.93) and power-law function (r 2 = 0.98), respectively.…”
Section: Residence and Flushing Timesmentioning
confidence: 99%
“…Finding a general regression relationship between the residence time and the freshwater input would be helpful in understanding the physical and hydrological processes in the estuary. Huang et al [40] conducted regression analyses between estuarine residence time and freshwater input using a power-law function in Little Manatee River, Florida. The authors found that regression by the power law provided a better fit compared to an exponential function.…”
Section: Residence Time In Response To Sea Level Risementioning
confidence: 99%